Golok-Golok Menthok: Exploring The Relationship of Religion and Culture in Transmitting Gender Equality Values - Yusrina, Jihan Avie; Niswah, Nujumun; Rubai, Rubai (Universitas Wahid Hasyim Semarang, 2024)
AbstractThis research is motivated by the stagnation of Indonesia's gender equality index score, which ranks 87 out of 146 countries, the strong influence of patriarchal values, and the high rate of gender-based violence. This condition demands a more practical approach to promoting gender equality, primarily through inclusive education from an early age. The golok-golok menthok tradition in Kudus, Central Java, was chosen as the object of study because it has great potential to integrate gender equality values into people's daily lives. The purpose of this study is to explore how the golok-golok menthok tradition can be a medium for gender-inclusive education that promotes values of justice. The method used is a descriptive qualitative approach. The results show that the golok-golok menthok tradition not only functions as a religious celebration but also as a tool to transmit gender equality values to the younger generation. This tradition emphasizes that gender justice is part of a complete faith and must be integrated into daily life. The implications of this research show that culture and religion can synergize in promoting gender equality, forming a strong foundation for future generations to be fair and respectful of gender differences.